The Bigger Picture: Picking the Right Soap Box—Is it Possible to Connect with Different Audience Targets (Practitioners and Patients) from the Same Platform? - Abbass, Mohammed Ali A.; Keshava, Hari B.; Delaney, Conor P. (Clinics in Colon and Rectal Surgery, 2017)
The use of Internet and social media has skyrocketed in the past decade. It did not take long until physicians realized that they could use social media as a tool for communication with patients and colleagues. Since then use of social media has exploded and the information that has become available for physicians and their patients is remarkable. In addition, because of the immediacy of the platform, messages that are incorrect or not desired can be rapidly promoted, whether deliberately or accidentally. To obtain the best use of social media, the right platform should be chosen, and this varies depending on the group one is trying to reach, and the message or visibility desired. In this article, we review the variety of options available to users.
Keywords: surgery; platform; Facebook; YouTube; Twitter